Diamond-Gardner Syndrome: Autoerythrocyte Sensitization Syndrome - Nejat Akar; Zeynep Nur Karagöz; Yasemin Ardıçoğlu Akışın (Journal of Pediatric Research, 2019)

(untitled)
Diamond-Gardner syndrome (DGS) is an autoimmune disease characterized by painful ecchymoses that develop following emotional stress or trauma. The lesions are observed mostly in the extremities and these lesions are the result of autosensitization to extravasated erythrocytes after trauma. The majority of the patients diagnosed with this disease are composed of young women. In this case report, a teenager who had complaints of recurring painful ecchymoses with no related personal or familial background and later-diagnosed with DGS is presented. Although it is seen less commonly, DGS should be considered in the differential diagnosis of cutaneous lesions and haemorrhages of the childhood period, especially in adolescence.